The single nucleotide polymorphisms rs11761556 and rs12706832 of the leptin gene are associated with type 2 diabetes mellitus in the Iraqi population - Musafer, Karar N. J.; Huyop, Fahrul Z.; Ewadh, Mufeed J.; Supriyanto, Eko; Al-Thuwaini, Tahreer M.; Al-Shuhaib, Mohamed Baqur S (Archives of Biological Sciences, 2021)
Paper description: Three high-frequency single-nucleotide polymorphism (SNPs), rs11761556, rs12706832, and rs2167270, of leptin (LEP) gene were screened to investigate association with type 2 diabetes mellitus (T2DM) in Iraqi adults. Significant associations between only two SNPs (rs11761556 and rs12706832) variations and T2DM were observed. Individuals with AA genotype in rs11761556 and rs12706832 had higher body mass index waist circumference, fasting blood glucose, hemoglobin A1c, homeostatic model assessment for insulin resistance, insulin, low-density lipoprotein cholesterol, and triglyceride values than individuals with other genotypes. These LEP gene variations correlate with T2DM and may serve as a marker for assessment of T2DM in the study population. Abstract: This study was conducted to assess the potential association between leptin (LEP) gene polymorphisms and type 2 diabetes mellitus (T2DM) in Iraqi patients. Genomic DNA was extracted from 120 diabetic subjects and 100 controls. Three specific PCR fragments were designed to flank three highly frequent single nucleotide polymorphism (SNP)s within LEP, rs11761556, rs12706832 and rs2167270. The amplified loci were genotyped by PCR-single-strand conformation polymorphism (SSCP) followed by Sanger sequencing for representative genotypes. Logistic regression analysis was performed to detect the association between the targeted genetic variants and T2DM. PCR-SSCP genotyping showed three banding patterns for all three targeted SNPs. Individuals with the AA genotype in both rs11761556 and rs12706832 SNPs showed significantly higher (P<0.05) body mass index (BMI), waist circumference (WC), fasting blood glucose (FBG), hemoglobin A1c (HbA1c), homeostatic model assessment for insulin resistance (HOMA-IR), insulin, low-density lipoprotein cholesterol (LDL-C) and triglyceride (TG) values than those with other genotypes. Association analysis revealed that individuals with the A allele exhibited a greater risk of T2DM. Data of the present investigation indicated that both rs11761556 and rs12706832 SNPs exerted a noticeable association with T2DM. The study suggests implementing both rs11761556 and rs12706832 SNPs in the early detection of T2DM.